The community work: a physical proposal-recreational for the social prevention in children with dysfunctional conducts - Roberto Thompson-Herrera (Universidad de Guantánamo, 2012)
Social work in the Venezuelan context is one of the priorities that currently is implemented as part of the Bolivarian Revolution. This problem is determined to develop a study that aims to develop recreational physical activities and sports that influence the social prevention of dysfunctional behaviors in children of 8-10 years old, grounded in a conception for community social work. Different methods are used that allow theoretical and empirical research to develop contextualized mode to be applied in regions where problems of this nature occur.